Effectiveness of the Use of Manual and Electric Toothbrushes and the Effect of Educational Brushing Teeth with Video Animation on OHI-S Children with Down syndrome - Alivy Aulia Az Zahra; Natasha Winona Audrey; Devalna Siwi Ichyana; Tania Saskianti; Seno Pradopo; Sindy Cornelia Nelwan; Masyithah Masyithah (Faculty of Dental Medicine, Universitas Airlangga, 2021)
Background: Down Syndrome children have better ability in capturing instructions visually. The audio-visual learning method can be applied to Down Syndrome children. Electric toothbrushes were made to make it easier for them to brush their teeth, besides those electric toothbrushes have a handle that is comfortable to hold and control. Purpose: The purpose of this study is to determine the effectiveness of electric and manual toothbrushes on Down Syndrome children OHI-S scores and determine the effect of education on tooth brushing with animated videos on Down Syndrome children OHI-S scores. Methods: Subjects of the study were 34 Down Syndrome children aged 6-19 years in Surabaya, East Java, Indonesia. OHI-S scores were recorded before and after the subjects were educated to brush their teeth with animated videos or dental phantoms. OHI-S scores were also recorded before and after the subjects brushed their teeth using manual toothbrushes or electric toothbrushes. Results: The test results Independent T-test (p> 0.05) showed there was no significant difference between tooth brushing using a manual toothbrush and an electric toothbrush to the decline of OHI-S score of Down Syndrome children. The results of the Mann-Whitney statistical test were p> 0.05, that there was no significant difference in the reduction in OHI-S scores between Down Syndrome children who were educated with animated videos and dental phantoms. Conclusion: There was no significant difference between manual toothbrushes and electric toothbrushes and there was no significant influence of Down Syndrome OHI-S children who were educated with animated videos or dental phantoms.